2021
DOI: 10.1001/jama.2021.21392
|View full text |Cite
|
Sign up to set email alerts
|

Contraception Selection, Effectiveness, and Adverse Effects

Abstract: ontraception is defined as an intervention that reduces the chance of pregnancy after sexual intercourse. According to a report from 2013, an estimated 99% of women who have ever had sexual intercourse used at least 1 contraceptive method in their lifetime. 1 Approximately 88% of sexually active women not seeking pregnancy report using contraception at any given time. 2 All nonbarrier contraceptive methods require a prescription or initiation by a clinician. Therefore, contraception is a common reason women 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
111
0
11

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(123 citation statements)
references
References 95 publications
1
111
0
11
Order By: Relevance
“…Combined oral contraceptives (COC), which are a subset of combined hormonal contraceptives (CHC), typically contain an oestrogen and a progestin [ 2 ]. Progestins suppress the release of gonadotropin-releasing hormone from the hypothalamus, which prevents the secretion of luteinizing hormone from the pituitary, and subsequently, inhibits ovulation.…”
Section: Introductionmentioning
confidence: 99%
“…Combined oral contraceptives (COC), which are a subset of combined hormonal contraceptives (CHC), typically contain an oestrogen and a progestin [ 2 ]. Progestins suppress the release of gonadotropin-releasing hormone from the hypothalamus, which prevents the secretion of luteinizing hormone from the pituitary, and subsequently, inhibits ovulation.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Respondents indicated that they experienced more contraceptives. [8][9][10] Similar to previous studies, the injectable hormonal contraceptive method provides a greater change in the menstrual cycle than the pill type, so it is considered a risk factor for irregular vaginal bleeding patterns 8,11 12 Sustained amenorrhea causes changes in the menstrual cycle that cause some women to stop using injectable contraceptives, but many women accept the state of amenorrhea even though amenorrhea caused by progesterone administration is not known to be harmful. In addition to changes in the menstrual cycle in women, the use of injectable contraceptives, especially DMPA, can cause weight gain.…”
Section: Resultsmentioning
confidence: 99%
“…5 In healthy pregnancy-capable individuals without known prothrombotic conditions, use of oral CHCs is associated with an increased risk of venous thromboembolism from 2 to 10 per 100 000 to 7 to 10 per 100 000. 7 Although oral CHCs are commonly prescribed, often they are not an optimal contraceptive choice for individuals with CVD. 1,5 Estrogen-containing methods such as CHC pills, patches, or rings should generally be avoided in individuals with acquired or congenital CV conditions, which pose an increased risk of developing serious thromboembolic disease (eFigure in the Supplement).…”
Section: Safety Concerns With Hormonal Contraceptivesmentioning
confidence: 99%
“…Lipid profiles may be adversely affected in patients using CHCs (increased triglycerides) or depot medroxyprogesterone (increased low-density lipoprotein cholesterol). 5,7 There is limited evidence that CHCs may increase lipid levels or increase risk of myocardial infarction in women with known dyslipidemia. Given the significant limitations of the available data and the low rates of undiagnosed severe hyperlipidemia among women of childbearing age, screening for dyslipidemia is not required prior to initiation of CHCs.…”
Section: Safety Concerns With Hormonal Contraceptivesmentioning
confidence: 99%